Effects of interleukin-18 modulation on the pathogenesis of malaria infection - Jabbarzare, Marzieh (2013)
Malaria is an important parasitic infectious disease that afflicts mankind globally. The involvements of cytokines in the pathogenesis of malaria have well been documented and it has also been widely accepted that pro-inflammatory cytokines release plays crucial roles in the progression of severe pathology in malaria. Interleukin 18 (IL-18) is an important mediator which functions as an immune regulator and inducer of pro-inflammatory cytokines release. Activation of IL-18 in the immune system has been shown to amplify inflammatory responses in many disease conditions and may play a crucial role in the development of certain disease. This study is designed to determine the role and involvement of IL-18 during malaria infection and the effects of modulating its release on the course of the infection, the release of major pro- and anti-inflammatory cytokines and also the histopathological consequences in major affected organs during the infection. Male ICR mice infected with Plasmodium berghei (P. berghei) ANKA were used as malaria model in this study. Mice were injected intraperitoneally with 2 x 107 infected red blood cells. Plasma IL-18 concentrations in malaria-infected mice as measured by ELISA method, showed continuous increment from the beginning to the end of the infection. Release phase was found to be dependent on the level of severity of the infection. Modulation of the release of IL-18 was carried out by treating the malaria infected mice with recombinant mouse IL-18 (rmIL-18) and recombinant mouse IL-18 Fc chimera (rmIL-18 Fc chimera) intravenously. Inhibition of IL-18 release by rmIL-18 Fc chimera have delayed the emergence of the physical signs of infection and the development of parasitemia, subsequently prolonging the life span of mice infected with malaria. Augmentation of systemic IL-18 with rmIL-18 significantly decreased the release of anti-inflammatory cytokine (IL-10), whereas, inhibition of IL-18 with rmIL-18 Fc chimera showed increased level of IL-10. A significant elevation of pro-inflammatory cytokines (TNFα, IFNƴ, IL-1α and IL-6) was also observed during augmentation of IL-18 level. Nonetheless, these pro-inflammatory cytokines decreased during inhibition of IL-18 by rmIL-18 Fc chimera. From the pattern of cytokines release, it can be suggested that IL-18 exerts a pro-inflammatory activity in the Th1 type response by signaling the production of IFNƴ during malaria. Histopathological analysis performed on major organs known to be affected during malaria infection which include the brain, lungs, liver, spleen and kidneys of malarial mice showed significant histopathological changes in all organs of malarial mice. Treatment with rmIL-18 Fc chimera showed significant improvement on the histopathological conditions of the organs as compared to the malarial mice treated with PBS. However, mice treated with recombinant mouse IL-18 showed severe and worsening histopathology during the infection. In conclusion, the results from this study suggest that IL-18 may well play a crucial role in mediating the severity of malaria infection and it may play a key pro-inflammatory role throughout immune response against the disease. Antagonizing IL-18 activity has improved the histopathological conditions associated with the disease which may well suggest that targetting IL-18 would provide a potentially significant therapeutic benefit in malaria therapy.